Effect of spindle speed and feed per tooth in feed rate perspective on inconel HX cutting force / N. A. Mohd Nor ... [et al.] - Mohd Nor, N. A.; Kamarulzaman, N. F.; Zakaria, N. A. S.; Awang, N.; Baharudin, B. T. H. T.; Mohd Ariffin, M. K. A.; Leman, Z. (Universiti Teknologi MARA, 2021)
Reducing feed rate during end-milling of nickel-based superalloys for lowcutting force has always been a common approach. This is due to these alloys having superior properties, making them widely regarded as difficultto-machine materials. As feed rate is tied to spindle speed and feed per tooth, it is crucial to comprehend whether spindle speed, feed per tooth or the interaction between spindle speed and feed per tooth has a significant factor on cutting force reduction when increasing the feed rate. Accordingly, this manuscript presents an effect of spindle speed and feed per tooth in feed rate perspective on Inconel HX cutting force. Half-immersion down-milling and full-immersion down-milling was conducted experimentally using solid ceramic end-mill cutter. The results indicate that cutting force decreases and then increases after further increase in spindle speed, while cutting force increases with an increase in feed per tooth. Optimum spindle speed and optimum feed per tooth for low-cutting force were 21,400 rpm and 0.013 mm/tooth. Furthermore, feed per tooth was the significant factor which influenced the cutting force, whereas spindle speed, and the interaction between spindle speed and feed per tooth were not significant.